PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK - Eza Ezila Eddy (Departemen Matematika, 2018)
one of cognitive competence that can be owned by student is the competency of understanding mathematical concepts in learning mathematics. In fact, the competency of understanding mathematical concepts of students grade VIII SMP Negeri 31 Padang is still low, so it needs to be increased. One of the effort to overcome this problem is by applying Two Stay Two Stray (TSTS) type of cooperative learning model to make student understand the material and can build the knowledge by themselves. Thus, this why alone research to describe is student’s concept understanding using TSTS type of cooperative learning model better than student’s understanding konsep using conventional learning in grade VIII SMP Negeri 31 Padang. Base on data analysis, can be concluded that student’s understanding concept using TSTS type of cooperative learning model is better that student’s understanding concept using conventional learning.Keywords– TSTS, cooperative learning model, mathematical concepts understanding